Diagnóstico ambiental no período frio e seco do Córrego Bandeirantes, município de Rio Claro, SP: parâmetros físicos, químicos e físico-químicos - Canedo, Sertório Nogueira [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
The present study was concerned with checking the water quality, the recovery of the riparian vegetation and vegetation around the springhead of stream Bandeirantes, such as the inadequate disposal of waste along this stream, which is located in Rio Claro, SP, in the period from March to July of 2010. Aiming to propose mitigation measures to reverse the degradation processes and develop activities to help a better awareness of the population directly related to this water resource. The water quality was analyzed by performing monthly sampling in three different points along the stream. The first point of sampling is in the spring of the stream, the second at the region called estradão and the third near its mouth, when it flows into the Ribeirão Claro, a tributary of the right bank of the Corumbataí river. It was calculated from the Water Quality Index (WQI) developed by Cetesb. The results were compared with current law. The riparian vegetation, which is responsible for the protection of rivers and streams, was observed and examined during the field work. The results indicated the stream as class 2 and the WQI has been classified, in the most of the analysis, such as a water of good quality. However, some parameters showed a worrying situation and highlighted the current situation, with waste deposits, furniture and animal waste into the pit of the stream studied

Este estudo se preocupou em verificar a qualidade da água, a questão da recuperação da mata ciliar e da vegetação do entorno da nascente e a disposição inadequada de resíduos ao longo da cava do Córrego Bandeirantes, município de Rio Claro, no período de março a julho de 2010. Foram feitas análises da qualidade da água realizando coletas mensais em 3 pontos distintos ao longo do córrego Bandeirantes. O primeiro ponto de coleta foi a nascente do córrego, o segundo na altura da região denominada “estradão” e o terceiro, próximo a sua foz, quando desemboca no Ribeirão Claro, afluente da margem direita do rio Corumbataí. Foi realizado o cálculo do Índice de Qualidade das Águas (IQA) desenvolvido pela Cetesb. Os resultados obtidos foram comparados com a legislação vigente. A mata ciliar, que tem o papel de proteção dos corpos de água, foi observada e analisada durante saídas de campo. Os resultados obtidos enquadram o córrego como classe 2 e o IQA foi classificado, na maioria das análises, como água de qualidade boa. No entanto, alguns parâmetros indicaram uma situação preocupante e evidenciaram a atual situação, encontrando-se depósitos de lixo, móveis e resíduos animais dentro da cava do córrego estudado
Keywords: Engenharia ambiental; Água - Qualidade; Mata ciliar; Bacias hidrograficas; Corumbatai (SP); Bacia do Corumbataí